(untitled) (Revista de Investigaciones Universidad del Quindío, 2019)
The CYNERGIA research group, through its hotbed MERCATORIA I, analyzed the history of the problem of access to land in Colombia. To increase the sharecropping contract appears as a just application for the Colombia in the post-conflict period in Colombia. This conclusion arrived after application of the dogmatic, rational and reflective method, for the historical, normative and legal foundations at the national and international level. We conclude that sharecropping is a valid option to achieve access and distribution of land, avoiding violence.